A CONCEPTUAL FRAMEWORK FOR THE CARE OF THE CHILDS FAMILY MEMBER WITH CONGENITAL HEART DISEASE, BASED ON ROYS THEORY - Daniele Laís Brandalize; Ivete Palmira Sanson Zagonel (Universidade Federal do Paraná, 2006)
This study searches to delineate a conceptual framework for the family member's care of the child with congenital heart disease, supported by Roy's theory, which offers conceptions that are grounded in the adaptation process and allows the understanding of the being as a wholly affected person. It describes the concepts that permeate the conceptual framework and its application in a specific care area of the family member of the child with congenital heart disease. It makes clear that the transitional care favors the parent to undergo the child's health-disease transition, once it involves behaviors that enable personalized, individualized care, helping the being to accomplish a harmonious process with development of his/her potential to regain the lost balance.